Inflation targeting and the role of exchange rate pass-through - Reginaldo Pinto Nogueira (University of Kent, Department of Economics, 2006)
The paper presents evidence on the exchange rate pass-through for a set of emerging and developed economies before and after the adoption of Inflation Targeting. We use an ARDL model for a sample of developed and emerging market economies to estimate the short-run and the long-run effects of depreciations on prices. The results support the view of the previous literature that the pass-through is higher for emerging than for developed economies, and that it has decreased after the adoption of Inflation Targeting. This reduction, however, does not mean that the pass-through is no longer existent for developed and emerging market economies, especially when it comes to the long-run. This finding highlights the importance of using dynamic models when dealing with the inflation-depreciation relationship. The results also show the important role of foreign producer costs for the imports pricing behaviour in developed economies, and of inflation stability in emerging markets.
Keywords: E31; E52; F31; F41; 330; Inflation Targeting; Exchange Rate Pass-Through